Soybean and Rice-Bran Oil blended Biodiesel Production and Performance Test on 4-Stroke Single Cylinder Diesel Engine - Tripathi B.M.; Shukla S.K. (My University, 2025)
This article presents the production and performance analysis of biodiesel from a blended oil comprising 20% soybean oil and 80% rice bran oil. The production process utilizes transesterification with methanol and NaOH, and the biodiesel synthesis time is optimized using a homogenizer. The biodiesel is tested on a four-stroke single-cylinder internal combustion (IC) engine, where key parameters such as brake thermal efficiency and specific fuel consumption are measured. The study compares the performance of biodiesel derived from the blended oil with biodiesel produced from pure soybean oil. Experimental results reveal that the biodiesel from the blended oil offers higher efficiency. Specifically, the brake thermal efficiency of the blended biodiesel increases with load, achieving values of 7.4%, 14.3%, 21.9%, and 23.6% at loads of 1kg, 2kg, 3kg, and 4kg, respectively. In terms of brake-specific fuel consumption, the blended biodiesel showed values of 2.425, 1.536, 1.168, and 0.989 kg/kW-hr for the same loads. The time required to consume 5 ml of blended biodiesel at a constant 1500 RPM decreases as the load increases, with times of 38.50, 35.72, 28.19, 24.72, and 21.88 seconds for loads of 1 kg, 2 kg, 3 kg, and 4 kg, respectively. The overall findings suggest that biodiesel from the rice bran and soybean oil blend is more efficient than pure soybean oil biodiesel, indicating its potential for more effective use in IC engines. © 2024 Widener University School of Civil Engineering. All rights reserved.